Einfluss von Prozessparametern auf die nichtwässrige Synthese von Titandioxid‐Nanopartikeln. Issue 3 (30th January 2014) - Zimmermann, Mandy; Garnweitner, Georg; Teipel, Ulrich; Weber, Alfred
<x xml:space="preserve">Abstract</x> The nonaqueous synthesis of TiO2 nanoparticles in benzyl alcohol in a 1.5‐L stainless steel reactor was investigated in detail regarding the influence of various process parameters. Thereby the reaction process was correlated with the development of the system pressure as a spontaneous pressure increase occurs parallel to the particle formation because of the release of water.